2019
DOI: 10.11622/smedj.2019130
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection of colonic lesions: first 50 cases at a local institution

Abstract: O r i g i n a l A r t i c l e 508 (ASA) class 1-3. Their median age was 60.0 years and the majority (n = 36) were male. The mean procedure time was 80.9 minutes. 36 (76.6%) of cases underwent en bloc resection. 4 (7.8%) cases required conversion to surgery, mainly due to difficulty in raising the colonic lesions. 3 (5.9%) patients had malignancy as the final histology. 2 (4.3%) patients had recurrence during surveillance scope. No cases of early mortality were reported.CONCLUSION Our results suggest that ESD f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Procedure time in the literature is variable, certainly as a function of lesion size. Our median procedure time of 62.5 min was within the range of what has been described in the literature, whereas our median lesion diameter of 4.00 cm and area of 10.05 cm 2 were larger than several other study populations 19,23–27 . Resections were efficient with a median efficiency of 6.86 min/cm 2 , although this metric is not widely reported.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Procedure time in the literature is variable, certainly as a function of lesion size. Our median procedure time of 62.5 min was within the range of what has been described in the literature, whereas our median lesion diameter of 4.00 cm and area of 10.05 cm 2 were larger than several other study populations 19,23–27 . Resections were efficient with a median efficiency of 6.86 min/cm 2 , although this metric is not widely reported.…”
Section: Discussionsupporting
confidence: 67%
“…Our median procedure time of 62.5 min was within the range of what has been described in the literature, whereas our median lesion diameter of 4.00 cm and area of 10.05 cm 2 were larger than several other study populations. 19,[23][24][25][26][27] Resections were efficient with a median efficiency of 6.86 min/cm 2 , although this metric is not widely reported. Complication rates were low, with a low incidence of perforation (microperforation in 0.9%) and bleeding (delayed bleed in 0.9%).…”
Section: Discussionmentioning
confidence: 95%
“…According to a single-center study in Japan, the mean ESD time was 46.4 minutes for 1199 lesions [17]. A study conducted by a Singapore group showed a mean time of 80.9 minutes with a median lesion size of 19.3 mm, showing that larger lesions require longer procedure times [27]. A study by a Korean group revealed a median time of 53.7 minutes for ESD, with a median lesion size of 21.1 mm [28].…”
Section: The Efficiency Of Esdmentioning
confidence: 99%
“…Tiing Leong Ang, FRCPEd, FAMS I n this issue of the Singapore Medical Journal, Koay et al (1) examined the role of narrow-band imaging (NBI), an image-enhanced endoscopy (IEE) technique, for the diagnosis of duodenal villous atrophy, while Li et al (2) and Tai et al (3) reported the early Singapore experience with colorectal endoscopic submucosal dissection (ESD). The aim of IEE as an adjunct to standard white light endoscopy is to improve endoscopic detection, characterisation and diagnosis of mucosal lesions.…”
Section: Gastrointestinal Neoplasiamentioning
confidence: 99%